Exploration on the High-Quality Development Path of Study Tour Practice Education in Hailin City ——Practical Innovation Based on the Integration of Red Study Tour and Technology Study Tour - Na Li; Lu Han; Yingying Song; Haifeng Dong (Education Research on Study Tours and Practice, 2026)
Under the background of the new era, study tour practice education serves as a key vehicle for implementing moral education and promoting quality education. Relying on its advantages in red culture, ecological resources, historical folklore, and technological industries, Hailin City takes the inheritance of red genes as the core and adopts the "red study tour +" integration approach to construct a "seven-color study tour" curriculum system. Through curriculum-based and project-based learning, it promotes the quality and efficiency of technology study tours, and builds a comprehensive study tour landscape through base construction, route planning, regional cooperation, and service upgrading. Practice shows that specialization, systematization, and branding are the core pathways for the high-quality development of county-level study tours. This paper systematically summarizes the model innovation, implementation mechanisms, and educational outcomes of Hailin’s study tour practice education, providing replicable and scalable practical samples and theoretical references for county-level study tour practice education nationwide.